The Parkinson’s disease-associated protein α-synuclein disrupts stress signaling – a possible implication for methamphetamine use? - Shaoxiao Wang; Stephan N. Witt (Microbial Cell)
The human neuronal protein α-synuclein (α-syn) has been linked by a plethora of studies as a causative factor in sporadic Parkinson’s disease (PD). To speed the pace of discovery about the biology and pathobiology of α-syn, organisms such as yeast, worms, and flies have been used to investigate the mechanisms by which elevated levels of α-syn are toxic to cells and to screen for drugs and genes that suppress this toxicity. We recently reported [Wang et al. Proc. Natl. Acad. Sci.(2012) 109: 16119–16124] that human α-syn, at high expression levels, disrupts stress-activated signal transduction pathways in both yeast and human neuroblastoma cells. Disruption of these signaling pathways ultimately leads to vulnerability to stress and to cell death. Here we discuss how the disruption of cell signaling by α-syn may have relevance to the parkinsonism that is associated with the abuse of the drug methamphetamine (meth).